Soft materials as biological and artificial membranes. (12th October 2021) - Tang, Shukun; Davoudi, Zahra; Wang, Guangtian; Xu, Zihao; Rehman, Tanzeel; Prominski, Aleksander; Tian, Bozhi; Bratlie, Kaitlin M.; Peng, Haisheng; Wang, Qun
Abstract : This review focuses on soft materials involved in biological and artificial membranes. The illustration is a conceptual scheme of artificial membranes synthesized by human-made hydrophilic and hydrophobic soft materials. Abstract : The past few decades have seen emerging growth in the field of soft materials for synthetic biology. This review focuses on soft materials involved in biological and artificial membranes. The biological membranes discussed here are mainly those involved in the structure and function of cells and organelles. As building blocks in medicine, non-native membranes including nanocarriers (NCs), especially liposomes and DQAsomes, and polymeric membranes for scaffolds are constructed from amphiphilic combinations of lipids, proteins, and carbohydrates. Artificial membranes can be prepared using synthetic, soft materials and molecules and then incorporated into structures through self-organization to form micelles or niosomes. The modification of artificial membranes can be realized using traditional chemical methods such as click reactions to target the delivery of NCs and control the release of therapeutics. The biomembrane, a lamellar structure inlaid with ion channels, receptors, lipid rafts, enzymes, and other functional units, separates cells and organelles from the environment. An active domain inserted into the membrane and organelles for energy conversion and cellular communication can target disease by changing the membrane's composition, structure, and fluidity and affecting the on/off status of the membrane gates. The biological membrane targets analyzing pathological mechanisms and curing complex diseases, which inspires us to create NCs with artificial membranes.